Personal development in the organization - Novak, Valentyna; Ilienko, Oksana; Lytvynenko, Larysa (Zeszyty Naukowe. Organizacja i Zarządzanie, 2017)
Most people almost entire adult life spends in organizations. Beginning in kindergarten and throughout their working lives, people, consciously or unconsciously, voluntarily or forcibly, with interest or apathy are fully included in the life of the organization, living by its laws, interact with other members of the organization, giving something to the organization, but also getting something in exchange [1].Entering the interaction with the organization, a person is interested in the various aspects of this interaction, that affect what he/she needs to sacrifice for the general organizational interests, what, when and in what extent he/she should do within the organization, conditions in which he/she should operate in the internal environment, with whom and how long interact, what to give the organization and others. On this and a number of other factors the satisfaction of human interaction with the organization, its relationship to the organization and contribute to the organization depend on.Setting boundaries between these parties of human interaction and interaction of organizations is one of the most important tasks of management, as it provides the basis for effective management in the organization.